The Role of the Sea and the Seafarers in Early Geodesy - Fischer, Irene K. (The International Hydrographic Review, 2015)
The mood of awe and wonder of the ancient Taoist Chuang Tzu contemplating the constancy of the vast ocean in its cont inuous change stands in stark contrast to our cu r ren t pride o f achievement in having tamed this mysterious infinity and cut it down to a finite size, a size where we can circumnavigate it, discover its secrets and exploit its riches. How did we get here from there ? It is relatively easy to be impressed by the stupendous technical developments of the recent decades and dismiss the earlier times condescendingly as ignorant and fumbling. Yet it may behoove us to take out a few minutes from our present technical hustle and bustle and try to appreciate and empathize with our ancestors ’ quest to cope with and understand their mysterious universe. Their first uncharted steps on the long road, after all, were the basis of our achievements, guided as these were by a long training in scientific-technical adaptations and extensions of precedents. As Lucan (1st cent.) already noted, even dwarfs perched on the shoulders of giants can see further than the giants themselves. Tracing the cultural achievements inherent in the beginnings of geodesy in ancient times is a rewarding experience as it gives a glimpse into another world. The present paper is the third in a trilogy (FlSCHER 1981, 1982) and concentrates on the sea. It is not intended here, however, to recount the developmental phases of ship building, navigation, marine geodesy, etc., through the centuries, but to gather some of the specific sea aspects hidden here and there in the general history of geodesy. Usually, until the recent fabulous growth of marine geodesy and the controversy of whether it should be considered as part of geodesy or as a new discipline by itself, the geodetic activities were taken to be inherently land-based. The obvious argument referred to its roots in the age-old need for cadasters and land surveyors, and the subsequent development of geodetic control nets on the continents. But this is only half the story. The other half derives from the just-as-old quest to know the size and shape of the Earth, and here water bodies are an integral part of the Earth ’s surface (about 71 %) Most significant, however, are the specifically geodetic questions which delineate geodesy from other earth-disciplines : “where ? what direction ? how far ?”, to which the sea made its characteristic contributions, hampered though they were until very recently by their special technical difficulties.